2022
DOI: 10.21203/rs.3.rs-1682034/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Amino Acid Changes in Fusion protein of Virulent Newcastle Disease Virus from vaccinated poultry in Nigerian Isolates

Abstract: The roles of Fusion gene in the virulence of Newcastle disease virus has been well established but the extent of its variation among the newly identified XIV, XVII and XVIII genotypes which are predominantly found in Central and West Africa have until recently been understudied and LaSota vaccine strain protection against mortality and morbidity against XIV genotype is the least reported. In this study, F gene of vNDV isolated from samples collected in Nigeria from chicken cadaver from vaccinated chicken flock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Seroprevalence investigations on birds carried out in several areas in Nigeria throughout the years revealed varied ranges from 38% to 74.3% [133]. In more recent seroprevalence studies (table 1), the figures have not considerably changed as the prevalence range from as low as 3.2% Sanni OOF, et al [134] to as high as 67.9% Snoeck CJ, et al [135], which goes to show that without a doubt, Newcastle disease (ND) is enzootic in Nigeria. Recently, attempts were made by using molecular techniques at defining the genotypes and molecular epidemiology of the circulating virus in West and Central Africa including Nigeria [93,[136][137][138].…”
Section: Epidemiology Of Newcastle Disease In Nigeriamentioning
confidence: 95%
See 1 more Smart Citation
“…Seroprevalence investigations on birds carried out in several areas in Nigeria throughout the years revealed varied ranges from 38% to 74.3% [133]. In more recent seroprevalence studies (table 1), the figures have not considerably changed as the prevalence range from as low as 3.2% Sanni OOF, et al [134] to as high as 67.9% Snoeck CJ, et al [135], which goes to show that without a doubt, Newcastle disease (ND) is enzootic in Nigeria. Recently, attempts were made by using molecular techniques at defining the genotypes and molecular epidemiology of the circulating virus in West and Central Africa including Nigeria [93,[136][137][138].…”
Section: Epidemiology Of Newcastle Disease In Nigeriamentioning
confidence: 95%
“…FAO revealed that one of the major constraints to the achievement of an effective poultry disease control strategy is the ignorance of poultry keepers on appropriate procedures such as vaccination, pen spacing, breeding, and withdrawal of sick birds. According to Okwor et al [134], farmers in Nigeria have paucity of information about disease prevention. Adam VY, et al [207] found that inadequate knowledge regarding the Newcastle disease virus, negative perceptions of ND, lack of basic training on animal health, preventive and control mechanisms all play a role in poor poultry management and increased disease outbreaks.…”
Section: Lack Of Education and Awarenessmentioning
confidence: 99%